(untitled) (CAHIERS MAGELLANES-NS, 2024)
Purpose:The purpose of this study was to examine the effect of self-Myofascial Release (MFR) and self-Bent Leg Raise (BLR) stretching on hamstring flexibility and fitness parameters before and after plyometric training sessions in beginner runners. Study Design: An experimental study. Objectives:To evaluate the effects of self-MFR and self-BLR stretching combined with plyometric training on hamstring tightness, endurance, strength, and agility. Methodology:Sixty-four subjects aged 18-25 were included in this study. Athletes were selected based on inclusion criteria and were randomly divided into two groups. The experimental group received self-MFR for 6 weeks, with three sessions per week, along with plyometric training. The control group received self-BLR for 6 weeks, with three sessions per week. Outcome measures included the rate of perceived exertion scale, active knee extension test, agility T-test, and leg press test. Results:Data analysis using paired t-tests and unpaired t-tests revealed no significant differences between pre and post hamstring tightness, endurance, agility, and strength in both groups. However, the experimental group (self-MFR) showed more significant improvements compared to the control group (self-BLR). Conclusion:The study concluded that the self-Myofascial Release technique combined with plyometric training is more effective than the self-Bent Leg Raise technique combined with plyometric training in improving hamstring flexibility and fitness parameters in beginner runners.